The Utilization Of The Wonorejo Site As A History Learning Resource: A Descriptive Study On Local Wisdom Based Education - Alfi Maqfiroh; Siti Zazak Soraya; Nastiti Mufidah (Faculty of Social Science, Universitas Negeri Padang, 2026)
This study discusses the Wonorejo Site as a resource for student history learning and its contribution to instilling local wisdom values. This research applied a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation. The primary data were obtained from the site caretaker, while additional data were collected from books, journals, and online sources. The data analysis technique employed an interactive model with three stages: data condensation, data presentation, and conclusion drawing. The validity of the data was ensured through source triangulation, which involved comparing data obtained from multiple sources, as well as through researcher’s diligence. The results show that the Wonorejo Site is used as a social studies learning laboratory through observation activities, video documentation, anda report preparation. This study aims to examine the use of the Wonorejo Site as a history learning resurce and its contribution to instilling local wisdom values in students. The results show that the Wonorejo Site is used as a social studies learning laboratory through observation activities, video documentation, and report preparation. Through direct learning activities at the site, students can gain a concrete understanding of history. It develops a sense of curioasity and they helps themleam to appreciate their cultural heritage.